A review of edible saturniidae (Lepidoptera) caterpillars in Africa - Elizabeth Siago Kusia; Christian Borgemeister; Sevgan Subramanian (CABI Agriculture and Bioscience)
Abstract Background Edible saturniids constitute an important component of traditional diets in sub-Saharan Africa. They are also a source of livelihood for many rural communities both as food and as a source of income. Main body This review compiles information on the diversity, distribution, decimating factors, nutrition and conservation concerns of edible saturniids. A compilation of nutritional profiles, amino-acids, mineral and fat content of saturniids is presented. Details of edible saturniids consumption and food plants are listed as well as vernacular names in different parts of Africa. A comparison of collection, processing, storage and trading methods based on available literature is also included. Processing, which is mostly carried out by women, involves tedious and time-consuming methods that need to be improved. Poor handling and storage cause bacterial and fungal contamination that raises food safety concerns. An in-depth discussion of conservation concerns and possible interventions is also provided. Conclusion We conclude that edible saturniids are a source of highly nutritious food and incomes to many households in SSA, but wild harvesting is increasingly becoming unsustainable. We also conclude that the seasonal nature of availability limits their potential for profitable trade Further research on rearing edible saturniids is required since wild harvesting is unsustainable. Training women and youth on mass production technologies will ensure continuous supply of the insects and help preserve their natural habitats.